Long-term effect of anesthesia choice on patients with hepatocellular carcinoma undergoing open liver resection - Zhao, Runzhi; Xu, Xiyuan; Sun, Li; Zhang, Guohua (Frontiers in Oncology, 2023)
Clinical and experimental evidence suggested that anesthesia choice can influence cancer progression and patients’ outcomes by modulating tumor microenvironment and tumorigenic pathways. Curative resection is the mainstay of therapy for hepatocellular carcinoma (HCC), which is an intractable disease due to high recurrence and poor prognosis. However, different anesthetics may play different roles in alleviating surgery-induced stress response and inflammatory cytokines release that are considered to be closely associated with proliferation, invasion and metastasis of tumor cells. Propofol, sevoflurane, non-steroidal anti-inflammatory drugs and local anesthetics have shown to exert anti-tumor effect on HCC mainly through regulating microRNAs or signaling pathways, while other inhalational agents, dexmedetomidine and opioids have the potential to promote tumor growth. In terms of anesthetic methods and analgesia strategies, propofol based total intravenous anesthesia and thoracic epidural analgesia could be preferred for HCC patients undergoing open liver resection rather than inhalational anesthesia. Local anesthesia techniques have great potential to attenuate perioperative stress response, hence they may contribute to more favorable outcomes. This review summarized the relations between different anesthesia choices and HCC patients’ long-term outcomes as well as their underlying mechanisms. Due to the complexity of molecules interactions and signaling pathways, further studies are warranted to confirm these results so as to optimize anesthesia strategy for HCC patients.